Melatonin may suppress lung adenocarcinoma progression via regulation of the circular noncoding RNA hsa_circ_0017109/miR‐135b‐3p/TOX3 axis. Issue 2 (12th June 2022) - Wang, Yuanyong; Wang, Zhaoyang; Shao, Changjian; Lu, Guofang; Xie, Mei; Wang, Jian; Duan, Hongtao; Li, Xiaofei; Yu, Wanpeng; Duan, Weixun; Yan, Xiaolong
Abstract: Melatonin is a hormone synthesized in the pineal gland and has widespread physiological and pharmacological functions. Moreover, it can activate protective receptor‐dependent processes. These processes can prevent tissue carcinogenesis and inhibit malignant tumor progression and metastasis. Therefore, we investigated the regulatory effects of melatonin on dysregulated circular RNAs in human lung adenocarcinoma (LUAD) cells. In this study, we treated LUAD cells with melatonin and measured the expression of hsa_circ_0017109, miR‐135b‐3p, and TOX3 by quantitative reverse transcription polymerase chain reaction. Colony formation and cell counting kit‐8 assays were used to determine cell proliferation. The wound‐healing assay and Transwell experiment were carried out to evaluate the migration potential and invasive capacity of LUAD cells. Also, cell apoptosis was detected using a cell apoptosis kit, and protein production was identified by Western blot. It was suggested that melatonin could inhibit LUAD progression in vivo and in vitro, and the role of TOX3 in this process was explored. Additionally, hsa_circ_0017109 was found to sponge miR‐135b‐3p, a downstream factor of circ_0017109, which was demonstrated to target TOX3 in LUAD cells and could promote the Hippo pathway and epithelial–mesenchymal transition pathway. To summarize, we demonstrated that melatonin decreases the expression of circ_0017109 and suppresses the non‐small‐cell lung cancer cell migration, invasion, and proliferation through decreasing TOX3 expression via direct activation of miR‐135b‐3p.